A relação eu-outro na coordenação pedagógica: entre costuras e rupturas - Bassotto, Simone Aparecida Silva Angelo (2020)
This research sought to analyse how the pedagogical coordinators understand the role of interpersonal relationships in the constituition, and how these relationships reverberate in its professional performance.It shows as objectives: to identify how they perceive the role of interpersonal relationships in the performance of their functions; identify feelings and indutives situations that permeate the coordinators' narratives; analyze critical incidents provocativer of learning. It is a qualitative approach investigation, which used itself of narrative approach because it believes that this mode of research would allow access to the coordinators' professional experiences and subjectivities, with regard to interpersonal relationships. The participating subjects were two pedagogical coordinators of the education network in the county of São Paulo. The theoretical foundation was based on Wallonian Psychogenetics and on authors in the field of education whose studies are focused on teacher training and professional development, among which: Almeida, Placco, Canário, André, Souza, Bolívar, Mahoney, Prandini. For the production of the information, interviews were conducted inspired by the reflexive modality (SZYMANSKY, 2018). The information produced was analyzed according to the guidelines of Almeida (2012), aiming to seek to apprehend the individual entirely from the text produced in the interviews. The results of the research reveal that the coordinators understand that interpersonal relationships are part of the coordinator's work at school, and that when entering the school unit, they face difficulties of various orders within the scope of interpersonal relationships, however, it is in the course of performance coordinators find strategies to improve their performance. Inducing feelings and situations were identified, as well as critical incidents that caused changes in the coordinators' professional lives